(3bQGAGJ GLJeGYjI (B/s - (3NhTj, SYGOs ((3GdLRGFQ (B:s (3cfhR GdMceI ddfTQ h GdJhRjY ,s, 2022)
(3jMGhd ef NdGd gPG GdcJGH GdPj jHjf GjOjfG GdJWQb Gdi eNJda GdehGVjY Gh GdXhGgQ GdJj jYjTgG GdeLJeY GdLRGFQj Ydi ZQGQ HGbj GdeLJeYGJ h GdJj SjJe JbOjegG Ydi Tcd eLehYI ef GdebGdGJs
(3HHdjhZQGajG (B: (3U(B.104-105s
Keywords: (3GdJQHjIs; (3GdKbGaIs; (3Yde GdELJeGYs